Upaya Masyarakat Dalam Publikasi Destinasi Wisata Untuk Peningkatan Ekonomi Desa Leuwikujang Kec. Leuwimunding Kab. Majalengka - Mohammad Ridwan (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2020)
Leuwikujang Village, Leuwimunding District, Majalengka Regency, is a village that continues to grow rapidly and is often a model village, especially in the Leuwimunding district. One of the successes of the leuwikujang village was divided into two categories, the first being in the economic sector, there were opaque entrepreneurs, lanterns, tofu and woven bamboo craftsmen (boboko). The second area of ​​tourism is the existence of tourist sites evidence of cibaringkeung, sahuyangdora, kayas hills and Bandung well sites. Seeing the potential of so many villages and can improve the economy of the surrounding community allows the leuwikujang village to be the best village in majalengka. This research uses descriptive qualitative research methods. Based on the results of research conducted concluded as follows: 1. Community efforts in the publication of tourist destinations to improve the economy Leuwikujang Village Leuwimunding District Majalengka Regency is by promoting tourism in the village through social media, mass media, newspapers and others. Open opportunities for private parties to invest, and the promotion of attractions from the District Tourism Office. Improving the quality of human resources around attractions as a basis for tourism development and publication. 2. Tourist destinations located in the leuwikujang village, leuwimunding district, Majalengka Regency which are suitable for publication at the national level include Cibaringkeung Hill, Sahyuangdora evidence, Kayas evidence, Bandung Well Site and Community Craft Business or home industry which include Opak Food Business, Lantern Business, Business Venture Boboko and Leuwikujang Tofu Business. Keywords: travel destination publication, improvement, economy Abstrak Desa Leuwikujang Kecamatan Leuwimunding Kabupaten Majalengka, merupakan desa yang terus berkembang pesat dan kerap menjadi desa percontohan khususnya di wilayah kecamatan Leuwimunding. Salah satu keberhasilan desa leuwikujang terbagi menjadi dua kategori yang pertama bidang ekonomi adanya pengusaha opak, lentera, tahu dan pengrajin anyaman bambu (boboko). Yang kedua bidang pariwisata adanya obyek wisata situs bukti cibaringkeung, sahuyangdora, bukit kayas dan situs sumur bandung. Melihat potensi desa yang begitu banyak dan dapat meningkatkan perekonomian masyarakat sekitar memungkinkan desa leuwikujang menjadi desa terbaik di majalengka.Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Berdasarkan hasil penelitian yang dilaksanakan disimpulkan sebagai berikut : 1. Upaya masyarakat dalam publikasi destinasi wisata untuk peningkatan ekonomi Desa Leuwikujang Kecamatan Leuwimunding Kabupaten Majalengka adalah dengan cara mempromosikan wisata-wisata yang ada di desa melalui media sosial, media masa, koran dan lain-lain. Membuka kesempatan bagi pihak swasta untuk berinvestasi, dan adanya promosi objek wisata dari Dinas Pariwisata Kabupaten. Meningkatkan kualitas sumber daya manusia sekitar objek wisata sebagai modal dasar pengembangan dan publikasi wisata. 2. Destinasi wisata yang terletak di desa leuwikujang kecamatan leuwimunding kabupaten majalengka yang layak untuk dipublikasikan di tingkat nasional diantaranya Bukit Cibaringkeung, Bukti Sahyuangdora, Bukti Kayas, Situs Sumur Bandung dan Usaha Kerajinan Masyarakat atau home industri yang meliputi Usaha Makanan Opak, Usaha Lentera, Usaha Boboko dan Usaha Tahu Leuwikujang. Kata Kunci: publikasi destinasi wisata, peningkatan, ekonomi